Social capital of organizations - Gabbay, Shaul M.; Leenders, Roger Th. A. J. (Research in the sociology of organizations ;, 2001)
An influential concept in the social science literature, the theory of social capital, asserts that social actors gain resources through relationships with other actors. While social capital research has largely focused on individuals as the unit of analysis, this volume looks at social capital of organizations, or Corporate Social Capital (CSC), exploring how and to what extent social networks facilitate or impede the attainment of organizational goals. This collection of papers posits a distinction between social structure and its outcomes, noting that while positive outcomes yield social capital, the structure can also prohibit and obstruct action, resulting instead in social liability. The contributing authors pay particular attention to the sets of social conditions that lead to either capital or liability, and succeed in setting a research agenda that looks toward more effective management of organizational social capital.